(untitled) (Englisia : Journal of Language, Education, and Humanities, 2025)
The integration of Islamic values into English Language Teaching (ELT) poses significant challenges for teachers in Islamic schools. This study examines the obstacles and requirements associated with embedding Islamic principles into ELT at SMP IICP Puncak Darussalam. A needs analysis was conducted with students to explore their motivations, learning objectives, and challenges in language acquisition. The findings indicate that students primarily struggle with listening comprehension and speaking skills. To address these issues, the study recommends adopting a task-based approach, communicative language teaching, role-playing activities, and interactive listening exercises incorporating digital media to enhance engagement and align with students’ goals. These findings are expected to inform the development of effective ELT strategies in Islamic schools, particularly at SMP Puncak Darussalam, fostering more impactful teaching practices.